Innovative pan-tumor target strategy for CAR-T therapy: cancer-specific exons as novel targets for pediatric solid and brain tumors - Yuqing Luo; Jianqiao Shentu; Hening Xu; Yongming Xia; Lili Fang; Shiwei Duan (Journal of Translational Medicine)
Abstract Chimeric antigen receptor T-cell (CAR-T) immunotherapy has achieved remarkable success in treating chemotherapy-refractory hematological malignancies. However, its efficacy in solid and brain tumors remains limited due to challenges such as insufficient target antigens, poor T-cell adaptability, inefficient tumor site trafficking, and the immunosuppressive tumor microenvironment. To address these challenges, Shaw and colleagues proposed an innovative strategy targeting cancer-specific exons (CSEs) in pediatric solid and brain tumors. Using RNA sequencing data from 16 tumor types, the study identified 157 highly tumor-specific targets, including both known and novel proteins. The researchers validated several targets, including FN1 and COL11A1, demonstrating their therapeutic potential in in vitro and in vivo models. The study's approach of integrating exon-level analysis with a broad search for extracellular matrix proteins offers a new frontier for CAR-T therapy, providing valuable insights for improving immunotherapy in pediatric solid tumors. Although promising, the study also highlights the need for further evaluation of tumor recurrence and CAR-T cell exhaustion. The identification of novel pan-tumor targets may revolutionize CAR-T therapy design and expand its application in pediatric cancer treatment.